Molecular Bureaucracy: Toxicological Information and Environmental Protection. Issue 3 (4th February 2019) - Hepler-Smith, Evan
Abstract: Legal and political claims about environmental chemicals typically address such substances on a molecule-by-molecule basis. This article argues that this approach is not determined solely by the nature of chemicals. Rather, it is the product of legal structures, administrative procedures, regulatory lists, information systems, and nomenclature conventions, which I collectively term "molecular bureaucracy." This article traces the development of molecular bureaucracy, a global framework of environmental governance grounded in American regulatory infrastructure, and its political and environmental consequences. It does so by following the history of per- and polyfluoroalkyl substances, synthetic chemicals in widespread use since the 1950s whose toxicity has become a prominent subject of research and public concern since the late 1990s. Molecular bureaucracy originated in a classification system based on molecular identity developed to make chemical information accessible to the late nineteenth-century synthetic chemicals industry. It came to structure environmental law and politics through, first, the efforts of 1960s US policy-makers to render toxic hazards subject to government control through computer-based information coordination and, second, a vision of chemical holism within the nascent US Environmental Protection Agency and the Toxic Substances Control Act, which sought to accommodate the global environment to rational administration by aggregating diverse toxic hazards and reframing them as abstract chemical substances. The history of molecular bureaucracy offers valuable insights for present-day efforts to ground toxic substances scholarship and politics in alternative conceptions of environmental chemicals.